The Role of External Fixation in Trauma and Reconstruction of the Mandible in the Age of Rigid Fixation - Kazi, Aasif A.; Lee, Thomas S.; Vincent, Aurora; Sokoya, Mofiyinfolu; Sheen, Derek; Ducic, Yadranko (Facial Plastic Surgery, 2019)
Internal rigid fixation is the gold-standard treatment for facial fractures, but there are some specific cases that are more amenable to external fixation (ex-fix) application. Herein, we discuss advantages and disadvantages to ex-fix in the modern treatment of comminuted mandible fractures, infected mandible fractures, fractures of the condylar region, oncologic mandibular resection, pediatric mandible fractures, and fractures in the edentulous patient.
Keywords: external fixation; mandible reconstruction; segmental mandibulectomy; mandible fractures; pediatric facial fractures